Convective initiation and maintenance processes of two back‐building mesoscale convective systems leading to heavy precipitation events in Southern Italy during HyMeX IOP 13. (20th July 2016) - Lee, K.‐O.; Flamant, C.; Ducrocq, V.; Duffourg, F.; Fourrié, N.; Davolio, S.
Abstract : During Intensive Observation Period 13 (15 to 16 October 2012) of the first Special Observing Period of the Hydrological cycle in the Mediterranean Experiment (HyMeX), Southern Italy (SI) was affected by two consecutive heavy precipitation events (HPEs). Both HPEs were associated with multi‐cell V‐shaped retrograde regeneration mesoscale convective systems (MCSs). The life cycle of two MCSs in connection with their dynamic and thermodynamic environments were analysed using a combination of ground‐based, airborne and spaceborne observations and numerical simulations. Rain gauges revealed that heavy precipitation occurred in two phases: the first one from 1300 to 1700 UTC (35 mm h −1 ) was caused by a V‐shaped system initiating over the Tyrrhenian Sea in the early morning of 15 October. Convection was triggered by the low‐level convergence between the southwesterlies ahead of an upper‐level trough positioned over southeastern France and very moist southerlies from the Strait of Sicily. The convection was favoured by high convective available potential energy (1500 J kg −1 ) resulting from warm and moist conditions at low levels associated with high sea surface temperatures in the Strait of Sicily. In addition, humidity at mid‐level was enriched by the presence of an elevated moisture plume from tropical Africa, favouring the efficiency of the convection to produce more precipitation. The second phase of heavy precipitation (2300 UTC on 15 October to 0200 UTC on 16 October, 34 mm h −1 ) was caused by a MCS initiating over Algeria around 1300 UTC, which subsequently travelled over the Strait of Sicily toward Sicily and SI. Convection was maintained by the combination of large low‐level moisture contents and a marked convergence ahead of the cold front. Unlike other MCSs forming in the same region earlier on that day, this huge V‐shaped system did affect SI because the strong upper‐level flow progressively backed from southwesterly to south southwesterly.